Thathwir Kitab al-Lughah al-‘Arabiyyah ‘Ala Asas al-Aghradh al-Iqtishadiyyah bi al-Madkhal al-Siyaqiy - Iswanto, Rahmat; Qomari, Nur (Institut Agama Islam Negeri Curup, 2023)
This research aimed to develop an Arabic language book for students of the Islamic Economics Department at the State Islamic Institute of Curup, based on economic purposes with a contextual approach. The model for teaching the Arabic language that had been used by the lecturer was found to be ineffective, as it did not integrate language and economic subject matters. Based on research on contextualized language learning, the researcher investigated the effectiveness of a contextual approach in teaching Arabic language to students in Islamic economics. This study aimed to answer the following research questions: how to develop an Arabic language book based on economic purposes with a contextual approach for students of the Islamic Economics Department at the State Islamic Institute of Curup? What is the impact of the Arabic language textbook on students' Arabic language competencies based on economic purposes with a contextual approach for the students of the Islamic Economics Department at the State Islamic Institute of Curup, Bengkulu? The research hypotheses suggested that the Arabic language book based on economic purposes with a contextual approach would effectively promote students' competencies in the Arabic language. This study sought to develop the aforesaid book with an experimental design to measure its impact. The results showed that the use of the Arabic language book significantly improved students' Arabic language skills and that the use of lesson materials accompanied by a dictionary was effective. This study provides insights into the importance of a contextual approach in teaching Arabic language to students in specific fields, such as Islamic economics.